Case report: Pancreatic metastasis from small-cell lung cancer appears as primary G2 pancreatic neuroendocrine tumor on combined contrast PET imaging with three probes - Zhang, Huimin; Gao, Jie; Cong, Xiaofeng; Chen, Chen; Yin, Jiaxin; Xiong, Wenji; Liu, Ziling (Frontiers in Oncology, 2024)
Pancreatic metastasis is a rare malignant tumor; when it comes to multiple cancers, it may be a challenge to identify the primary lesion of new pancreatic metastases. With the continuous advancement of imaging technology, the PET/computed tomography (CT) has been widely used because of its high diagnostic accuracy and non-invasiveness. However, in the present case, the patient had history of limited small-cell lung carcinoma and prostatic cancer; the combined application of the three kinds of PET/CT was used to identify the new metastases of pancreatic and bone metastases, which suggested a high probability of primary G2 pancreatic neuroendocrine tumor with bone metastases. After the needle biopsy, samples were confirmed by diagnostic pathology as small-cell lung cancer metastasizing to the pancreas and bone. The results of our case suggests the irreplaceability of pathology and possibility of misdiagnosis by PET/CT; moreover, it also supplements clinical data for second primary cancers after small-cell lung cancer.